Enzymatic Changes in Serum of Benign and Malignant Brain Tumors Patients - Kusay A. M. Al-Chalabi; Saba Z. Mahmood Al-Abachi (College of Education for Pure Sciences, 2008)
Abstract The present study is concerned with the investigation of the activity of some enzymes as lactate dehydrogenase (LDH), creatine kinase (CK), alkaline phosphatase (ALP), xanthine oxidase (XO), adenosine deaminase (ADA), cytidine deaminase (CDA), 5`-nucleotidase (5`-NT), deoxyribonuclease (DNase), in serum of benign and malignant brain tumor patients. Blood samples 93 from brain tumors patients, and 65 blood samples from healthy subjects as control group are collected for the present study. The results obtained indicated a significant increase in the activities of LDH, CK, CK-MB, ALP, XO, CDA, 5`-NT and DNase in serum of benign and malignant brain tumor patients compared with control group. A decrease in the activity of ADA was observed in malignant patients only.